A New Algorithm Technique for Protection Secure Personal Key and Cloud Storage - Waleed Abdulqahar, Assma (International Journal of Supply Chain Management, 2020)
Abstract People can only enjoy the completed advantages over astronaut computing condition we may address the entirely actual privateness or safety concerns that arrive with storing touchy private facts into databases and applications measure around the Internet. Cloud computing is the class of a computing rule the place the enormous dynamic up to expectation IT helps as like a "service" the usage of pc and web applied sciences is transferred in imitation of much out of doors customers. The proposed method offers three-level protection the usage of AES algorithm and a secure personal key. The approach also provides data tankage privateness safety because of huge groups yet the discovery about sensitive facts tankage leaks. Our order gives some on the privateness practices ancient within wind computing services.